Adolescents in a tuberculosis hospital: Qualitative study of how relationships with doctors, caregivers, and peers mediate their mental wellbeing. - Olga Zvonareva; Saskia Witte; Nadezhda Kabanets; Olga Filinyuk (PLoS ONE, 2021)
Lengthy hospitalization can impact adolescents' mental wellbeing in a number of negative ways. Scholarship has indicated that a young patient's relationships play an important role in reducing the amount of stress felt and in improving emotional state. In this article we turn to the experiences of adolescents with tuberculosis [TB] in Russia to explore how exactly hospitalization together with the TB diagnosis itself impact their mental wellbeing and how relationships with others mediate these impacts. We conducted a qualitative, interview-based study in Tomsk pediatric TB clinic. Interviews were conducted with three groups relevant for reaching the aim of this research: adolescent patients, their adult caregivers, and their treating physicians [17 informants in total]. Interview data were complemented with prolonged observations in the same clinic. The results of our study highlight that threats to mental wellbeing of adolescents with TB are multiple. Adolescents who are about to enter the in-patient treatment feel apprehensive and anxious about their future. They tend to have a hard time accepting their diagnosis, which they often feel is something shameful, and, consequently, may develop a negative attitude towards themselves. Most importantly, many undergo painful loss of personal relationships and expect or actually experience rejection by peers because of having tuberculosis. However, relationships with physicians, caregivers, and other patients in the clinic mediate negative impacts of TB diagnosis and hospitalization on adolescents' mental wellbeing and can open ways for providing support. Supportive practices include physicians leaving it up to adolescents to decide what they want to discuss and when, caregivers remaining available for contact and keeping regular communication, and other adolescents with TB proactively seeking contact with the newcomers and behaving in a non-judgmental way. These results can inform design of adolescent-friendly TB services.